Network governance concepts, theories, and applications - Kapucu, Naim 1969-; Hu, Qian (Public administration/Public policy, 2020)
"In this timely new book, authors Naim Kapucu and Qian Hu define and examine key concepts, propose exciting new theoretical frameworks to synthetize the fast-growing body of network research in public policy and administration, and provide detailed discussion of applications. Network Governance offers not only a much-needed systematic examination of existing knowledge, but it also goes much further than existing books by discussing the applications of networks in a wide range of management practice and policy domains-including natural resource management, environmental protection, public health, emergency and crisis management, law enforcement, transportation, and community and economic development. Chapters include understudied network research topics such as power and decision-making in interorganizational networks, virtual networks, global networks, and network analysis applications. What sets this book apart is the introduction of social network analysis and coverage of applications of social network analysis in the policy and management domains. PowerPoint slides and a sample syllabus are available for adopters on an accompanying website. Drawing on literature from sociology, policy sciences, organizational studies, and economics, this textbook will be required reading for courses on network governance, collaborative public management, cross-sector governance, and collaboration and partnerships in programs of public administration, public affairs, and public policy"--